IFRS Adoption in Colombian SMEs: An ethnographic study from an accounting management perspective - Contreras-Cuentas, Margarita María (2026)
Despite the relevance of International Financial Reporting Standards (IFRS) worldwide, the literature on the aspects that SMEs need to consider after adopting such standards is scant. This study addresses the need for identifying a model that helps to guide Chief Accountants, financial controllers, and managers in similar roles to managing accounting systems after IFRS adoption. We conducted a focused ethnographic study among 26 commercial SMEs in the Colombian Caribbean Region through 36 interviews with business leaders. Through an inductive-deductive approach and iterative triangulation of data and literature, we identify a Steering Model for Accounting Management in SMEs under IFRS. Our model considers contextspecific conditions such as uncertainty, technology, teamwork, processes, and controls. Furthermore, our model underscores two managerial aspects: 1) Key IFRS topics (i.e. revenue and receivables, cash and equivalents, fixed assets, and employee benefits) and 2) Leadership (i.e. family presence in the firm, as well as technological, integral, and accounting and management). Our study not only contributes to the existing literature on managerial practices dealing with the adoption of IRS in SMEs but also sheds light to practitioners on a topic that is engraved in their role functions.